The radius of unit graphs of rings - Li, Zhiqun; Su, Huadong (AIMS mathematics, 2021)
Let $ R $ be a ring with nonzero identity. The unit graph of $ R $ is a simple graph whose vertex set is $ R $ itself and two distinct vertices are adjacent if and only if their sum is a unit of $ R $. In this paper, we study the radius of unit graphs of rings. We prove that there exists a ring $ R $ such that the radius of unit graph can be any given positive integer. We also prove that the radius of unit graphs of self-injective rings are 1, 2, 3, $ ∞ $. We classify all self-injective rings via the radius of its unit graph. The radius of unit graphs of some ring extensions are also considered.